The human vestibulo-ocular reflex and compensatory saccades in schwannoma patients before and after vestibular nerve section. (June 2022) - Pogson, Jacob M.; Taylor, Rachael L.; Bradshaw, Andrew P.; McGarvie, Leigh; D'Souza, Mario; Flanagan, Sean; Kong, Jonathan; Biggs, Nigel; Shivalingam, Brindha; Greenberg, Simon; Croxson, Glen; Halmagyi, G. Michael; et al.
Highlights: In unoperated vestibular schwannoma, ipsilesional canals show decreased vestibulo-ocular reflex (VOR) gain and increased saccade amplitude and frequency. One week after unilateral vestibular deafferentation lesioned canal gains drop by 0.22–0.35 and first saccade frequency and amplitudes increase by 37% and 2.9°. The video head-impulse test excitation/dis-facilitation VOR asymmetry is less for the intact posterior canal than for the other canals. Abstract: Objective: To examine the vestibulo-ocular reflex (VOR) and compensatory-saccades before and after complete unilateral vestibular deafferentation (UVD). Methods: Forty patients were studied before and after surgery for vestibular or facial schwannoma using the video head-impulse test (vHIT) and multivariable regression. Results: Prior to UVD (median(IQR), 14(58.4) days), the average VOR-gain towards the lesioned -ear was lower than in normal for all semicircular canals (lateral, anterior, posterior: 0.69, 0.72, 0.49). One-week after UVD (5(3.0) days) VOR gains were further reduced (0.22, 0.37, 0.27), however, within one-year after UVD (171(125.0) days) the lesioned- ear VOR gains had slightly increased (+0.08, +0.11, +0.03), maximally for the anterior-canal. After UVD, the VOR gain asymmetry (gain towards minus away from intact-ear) was lower for the intact posterior-canal plane (0.56, 0.56, 0.22). For the lesioned canals, the frequency and amplitude of the first compensatory-saccade increased from 61–93% and 1.9–3.6° pre-surgery, to 98–99% and to 3.1–5.9° one-week post-surgery and remained unchanged over one-year; second saccade frequency and amplitude decreased over the same timespan. Conclusions: After UVD the high-acceleration VOR for the intact posterior-canal plane is more symmetrical than the other canals. First compensatory-saccades adapt within one week and subsequently change only marginally. Significance: Saccade compensation from surgical UVD is near complete by one-week.